The transformative potential of the Apocalypse of John - Paul B. Decock (Acta Theologica)
The transformative power of the Apocalypse of John is not situated in its prophetic predictions in the sense of information about the future but in its offer of divine wisdom by means of the symbolic scenes. The four types of symbols drawn by Gregory Baum from sociological traditions help to understand the transformative power of the symbols through which the possibility is offered to the hearers to see themselves and the world in new ways, to be able to discern between the ways of Babylon and the ways of Jerusalem. The transformation in view is not merely an individual and temporary one, but a cosmic, social and divine-human one in which perseverance in doing the works of Jesus to the end and holding on to the witness to/of Jesus (Rev 2:26; 12:17) play a crucial role.